Desmoplastic infantile ganglioglioma: case report - Avcı, Emel; Öztürk, Adil; Baba, Füsun; Torun, Fuat; Karabağ, Hamza; Yücetaş, Seyho (The Turkish Journal of Pediatrics, 2008)
Desmoplastic infantile gangliogliomas are very rarely encountered, large supratentorial masses, derived from neuroepithelial origin, which have cystic and solid components and contain cells with astrocytic and ganglionic differentiation. These tumors are benign tumors of childhood that become symptomatic when they reach giant sizes. Sixty cases of desmoplastic ganglioglioma have been reported to date. In the present study, a case of giant desmoplastic infantile ganglioglioma in a 22-month-old patient is presented, which had an aggressive radiological appearance in the midline and presented with atypical symptoms.